Leadership and human resource management: response to the COVID-19 outbreak - Sudarmo, Sudarmo (International research journal of management, IT and social sciences, 2020)
This project reviewed the potential for leadership and human resource management in response to the emergence of the COVID-19 pandemic. In any emergency in a country, the role of a leader with the ability and seriousness of human resource management is believed to be very important. To prove this belief, we have collected many-related literature, such as understanding deeply the aspects of leadership and HR management that have been applied successfully in various international contexts. How this leadership role with good management of HR is effectively applied. Because we conducted this study in the pandemic era, an era where restrictions on public movement are being treated, the method of data collection was through engine searches by relying on keyword utility, for example, "leadership potential", "HR management", "responding to the COVID-19 outbreak", and "qualitative studies". Because this study is categorized, we present the results of the study in the descriptive analysis method under the phenomenological approach. For the findings of this review study to meet the principles of validity and trustworthiness, we, the findings of this study, must be able to answer research questions.